Developing Children's Supplementary Literature Book Based On Character Education In Sixth Grade Of Elementary School - Rizka Nur Oktaviani; Endah Wening Subekti (Journal of Educational Science and Technology (EST), 2018)
This study aimed to develop children's supplementary literature book based on character education. This study described the process and quality in developing supplementary literature book based on character education. The quality of this book was reviewed based on the product and its use in the classroom. This study used a mixed method of qualitative and quantitative sequential exploratory model and 4D developmental model. The Developmental model consisted of defining, designing, and developing phases. The results showed that development process includes the defining stage by mapping learning needs as a result; the design stage with a draft of the book as aresult; and the development stage with the final model of children's develop children's supplementary literature book based on character education as a result. The quality of the book was known to form its component score. All categories were categorized as very eligible. The result of observations was 97% in teacher activity, 93% in teacher response, 95 % student activity, and 96 % in student responses. Based on learning mastery, students learning outcome was more than 72. Therefore, it can be concluded that the developed children's supplementary literature book based on character education was very feasible to use.